The Influence of Brand Image and Service Quality towards Purchase Intention and Its Impact on the Purchase Decision of Samsung Smartphone - Haro, Andrian; Oktaviana, Dinawati; Trimulia Dewi, Anugrah; Anisa, Wan; Suangkupon, Akmaluddin (KnE Social Sciences, 2020)
Samsung is the manufacturer smartphone that is already known by the community because of the use of advanced technologies. The purpose of these study are to examine the influence of brand image towards purchase intention of Samsung’s smartphone; the influence of service quality towards purchase intention of Samsung’s smartphone; and the influence of purchase intention towards purchase decision of Samsung’s smartphone. Sample selection method used is purposive sampling with the sample size of this study is 150 Samsung’s smartphone users who already visit to the Samsung’s outlet. The analysis data was used Structural Equation Modeling (SEM) through AMOS’s software. The results show that brand image has an influence on purchase intention, service quality has an influence on purchase intention, and purchase intention has an influence towards purchase decisions. This research provides recommendations to the producer of Samsung’s smartphone to create a product that is safe for the user, because if consumers feel goods which belongs to secure and worthy that the consumer will purchase the product. Keywords: brand image, service quality, purchase intention, purchase decision